Tingkat Kepuasan Konsumen Terhadap Kedai Kopi Lo.Co Collaborative Space di Kecamatan Coblong Kota Bandung - Syah, Mohamad Haikal Febrian; Trimo, Lucyana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Lo.Co Collaborative Space has been established for 3 years, starting from 2021 until now. In conducting its business, Lo.Co Collaborative Space is expected to endure competition with other competitors by focusing on customer orientation. This research aims to analyze consumer satisfaction. The population of this study is all consumers of Lo.Co Collaborative Space, and the sample selection in this research uses purposive sampling technique with 100 respondents. The research design used is a quantitative design with a descriptive survey research approach. Data analysis employs descriptive statistics, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The research results indicate that the majority of Lo.Co Collaborative Space consumers are aged 21-24 years, male, have completed high school education, and they are students, with an income of Rp2,500,000 - Rp5,000,000. The Customer Satisfaction Index (CSI) value is 85.44% or 0.854, indicating high satisfaction among consumers, while Importance Performance Analysis (IPA) shows that coffee flavor, clear communication, and store color or paint in line with the cafe concept are the main priorities for improvement to enhance consumer satisfaction.